Propuesta de un plan de gestión ambiental de la disponibilidad del recurso hidrogeológico, con relación al abastecimiento de agua en el espacio costero de El Coco : Carrillo, Guanacaste : Costa Rica - Orias Arguedas, Lidia María 1965-; Gómez Tristán, María 1978- ([San José], Costa Rica, 2011)
The present investigation was developed on the El Coco shore, on the district of Sardina!, Carrillo's canton, Guanacaste province. The subject area is the El Coco aquifers, which presens an accelerated urbanism, focused on the tourism activities that have increased the pressure under the hydrologic resources, due to the changes on the soil exploitation, and the rising of others economic activities, which also have encouraged the extraction from private water well without regulations. This situation has provoked high vulnerabilities of contamination upon the El Coco aquifers. There are not precedent investigations on hydrologic resources availability in environmental gestation plans, related to the water provision on the El Coco shore, neither in other districts of Carrillo canton, therefore the present investigation has an exploratory-diagnostic approaching. Secondary sources of information were used to analyze the geological and hydrologic characteristics of the subject, likewise, a historical analysis on the soil exploitation was run, in order to investigate the construction and transformation process on the El Coco shore. Aerial pictures from 1947, 1971 and 1998, were studied with photointerpretation and teledetection, along with satellite pictures from 2007, besides the setting of axis in situ thru GPS in 2009, in order to sequence and obtain four maps of the soil exploitation (1947, 1971, 1998 y 2009) by using SIG. Structured and open surveys were applied as primary source to get information regarding water utilization and gestation plans at El Coco, intended to potable water customers and local leaders. This investigation also evaluates the frame legalities upon the hydrologic resources in the El Coco shore, likewise, the consumption of water resources. It has identified and characterized network of water wells potentially sensitive to contamination which provide water to El Coco shore. Finally, an integral gestation model was proposed regarding...
Tesis (maestría profesional en geología con énfasis en gestión integral para el desarrollo de los geo-recursos)--Universidad de Costa Rica. Sistema de Estudios de Posgrado, 2011
Al texto le falta la hoja 74
Keywords: BAHIA EL COCO (COSTA RICA); RECURSOS HIDRICOS -- ADMINISTRACION; RECURSOS HIDRICOS -- ASPECTOS AMBIENTALES; RECURSOS HIDRICOS -- ASPECTOS LEGALES; PROTECCION DEL MEDIO AMBIENTE; DESARROLLO SOSTENIBLE; USO DE LA TIERRA; CONTAMINACION DEL AGUA; CALIDAD DEL AGUA; GEOLOGIA; HIDROGEOLOGIA; SISTEMA GLOBAL DE POSICIONAMIENTO; SISTEMAS DE INFORMACION GEOGRAFICA; INTERPRETACION DE FOTOGRAFIAS